Long-term administration of pegylated liposomal doxorubicin at almost twice the recommended lifetime dose in 10 years without cardiotoxicity in a Japanese patient with HIV-associated Kaposi sarcoma. Issue 2 (February 2020) - Yokota, Kazuhisa; Yotsumoto, Mihoko; Muramatsu, Takashi; Saito, Masuyoshi; Kamikubo, Yoshiko; Ichiki, Akito; Chikasawa, Yushi; Bingo, Masato; Hagiwara, Takeshi; Amano, Kagehiro; Fukutake, Katsuyuki
Abstract: We report a Japanese patient with HIV-associated Kaposi sarcoma (KS) who had many cutaneous KS lesions with extensive bilateral groin edema. As the KS was refractory to antiretroviral therapy and pegylated liposomal doxorubicin (PLD), he was administered PLD up to a cumulative dose of 940 mg/m 2 in 10 years, which exceeded the recommended lifetime dose (550 mg/m 2 ). However, the patient showed no major adverse events, including cardiotoxicity, and he eventually died of pancreatic cancer.